Peran Manajemen Sumber Daya Manusia dalamMengimplementasikan K3 di Tempat Kerja: TinjauanLiteratur - Andira, Riska Ayu; Akkas, Muhammad Alief; Akbar, M. Nur Andika; Muin, Nisma Aliyah (Annusfy : Journal of Multidisciplinary Research, 2025)
This study aims to analyze the role of Human Resource Management (HRM) in implementing Occupational Health and Safety (OHS) in the workplace through a literature review approach. The research was conducted by examining various scientific sources related to OHS policies, safety training, internal supervision, and safety culture development. The findings indicate that HRM plays a strategic role in the successful implementation of OHS through the formulation of safety policies, the provision of continuous training, monitoring compliance with standard operating procedures, and the development of a strong safety culture. Previous studies show that a well-structured OHS system can significantly reduce workplace accidents. Additionally, managerial commitment, worker involvement, and the availability of safety facilities are key factors influencing the effectiveness of OHS implementation. This study emphasizes that the success of OHS is not solely determined by regulatory compliance but also by the active role of HRM in managing workers’ behavior, knowledge, and adherence to safety procedures. Therefore, HRM must develop sustainable and adaptive safety strategies to enhance workplace safety comprehensively.